2006
DOI: 10.1007/s00464-006-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open repair of incisional and primary ventral hernia: results of a prospective randomized study

Abstract: Laparoscopic repair of incisional and ventral hernias is superior to open mesh repair in terms of significantly less blood loss, fewer complications, shorter hospital stay, and excellent cosmetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(156 citation statements)
references
References 34 publications
7
141
0
6
Order By: Relevance
“…19 In the underlying trial, the use of mesh was mandatory for all incisional hernia repairs, frequently using polypropyl-ene material in the sublay or intraperitoneal position. Shorter operative time for laparoscopic incisional hernia repair was reported by a number of recently published studies, 13,14,20,21 while other studies show no differences or longer operative times in the laparoscopic group. 22,23 In small incisional hernia, introduction of trocars and positioning of instruments can be time-consuming.…”
Section: Figure-2mentioning
confidence: 84%
See 2 more Smart Citations
“…19 In the underlying trial, the use of mesh was mandatory for all incisional hernia repairs, frequently using polypropyl-ene material in the sublay or intraperitoneal position. Shorter operative time for laparoscopic incisional hernia repair was reported by a number of recently published studies, 13,14,20,21 while other studies show no differences or longer operative times in the laparoscopic group. 22,23 In small incisional hernia, introduction of trocars and positioning of instruments can be time-consuming.…”
Section: Figure-2mentioning
confidence: 84%
“…Several small randomized studies reported no differences in postoperative pain after laparoscopic and open incisional hernia repair. 13,14,20 One trial reported reduced use of analgesics after laparoscopic repair. 21 Postoperative pain after incisional hernia repair often originates not from the hernia itself, but from the surrounding tissues.…”
Section: Figure-2mentioning
confidence: 99%
See 1 more Smart Citation
“…La mediana del diámetro mayor de los defectos reparados fue 6 cm (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). 67,7% de los defectos reparados correspondieron a hernias incisionales, un 26% (n = 33) de los casos eran recidivas de reparaciones anteriores, esteroidales y paracetamol por horario.…”
Section: Resultsunclassified
“…La introducción de la cirugía mínimamente invasiva, abrió la posibilidad de la reparación laparoscópica de las hernias ventrales. Diversos estudios han demostrado su superioridad frente a la cirugía abierta en términos de complicaciones, dolor postoperatorio y estadía hospitalaria 4 . En relación a la recidiva, las diferencias no son tan claras 5 y existe controversia respecto a los factores que determinan una mayor recidiva herniaria.…”
Section: Introductionunclassified